Expressão de microRNAs em amostras tumorais e linfonodais de câncer colorretal - Petrarca, Cristiane Rios (2016)
Introduction: Colorectal cancer is the third most common cancer in men and the second in women worldwide. It presents multifactorial, heterogeneous and complex etiopathogeny, still not fully elucidated. The evolution of the disease is often distinct from the exhaustive surgical and pathological staging, eventually (possibly) patients with focal disease develop an aggressive pattern presenting poor prognosis. Recent evidence shows the molecular heterogeneity of colorectal cancer. In this context the microRNAs (miRNAs), small non-coding RNAs (containing 19-25 nucleotides) capable of regulating gene expression in post-transcriptional level, have been identified with different expressions for numerous diseases, including cancer. Colorectal cancer shows change in expression of several miRNAs. These changes have been associated with the diagnosis, prognosis, gene expression, chemosensitivity and staging, being a potential biomarker. Methods: Clinical and pathological data of patients submited to surgical resection of the primary tumor and regional lymph nodes diagnosed from September 2002 to October 2011 have been reviewed and analyzed, and included in the colorectal cancer tumor bank of the São Lucas Hospital's Oncology Department - PUCRS. The analysis of the expression of miRNAs was performed in the laboratory of the Institute of Biotechnology of the Catholic University of Brasilia where they were analyzed in primary tumor and regional lymph nodes for descriptive purposes and versus the clinical-pathological data of the cases studied. The quantification analysis of the following miRNA (mir-570, mir-16, mir-338, Let-7, miR-1, miR-150, mir-183, mir-650 and mir-31) were determined by qPCR. Statistical analysis tests: Fisher's, Wilcoxon and Kruskal Wallis Exact, considered a significance level of 5%. Results: Of the 28 cases studied, 28.6% were less than 60 years old at diagnosis and 71.4% aged 60 or over. The average age was 66.7 years (26 to 86). The mean (average) follow-up (period, age) was 3.9 years (0 to 9), SD= 2.8 and a median of 4 years. The expression of miRNAs in the primary tumor (N=28) showed more homogeneous pattern, with a tendency to overexpression; whereas, in ill lymph nodes (N=15) this pattern was more heterogeneous, with mir-570, mir-338, mir-1, mir-183 and mir-31 being presented overexpressed and mir-16, Let-7, mir-150 and mir-650 with a more repressed expression. The suppressed expression of mir-570 was associated with mortality when evaluated in the primary tumor (N=28), where the prevalence of death in individuals with suppressed expression was 63.64% and those overexpressed was 17.65%, with p=0.020. In the primary tumor of patients with lymph node metastasis (N=15) the median expression of mir-183 was 4.42 with interquartile range (IQR) p25 of 1,66 and p75 of 43.01; whereas in the samples from patients with no ill lymph nodes (N=13) the median expression of mir-183 was 54.17 with IQR p25 of 13.12 and p75 of 223.14, with p=0.01, suggesting focal disease at diagnosis. In the subgroup of patients with lymph node metastasis (N=15), the expression of mir-650 in lymph node was associated with the prevalence of recurrence. The expression of mir-650 showed suppressed expression in 25% of the recurrence cases and was overexpressed in 85% of cases, with p=0.04. Conclusions: The expression pattern of miRNAs differs depending on the site of the disease studied (primary tumor or metastatic disease). The suppressed expression of mir-570 in the primary tumor is likely to be predictor of mortality. Overexpression of mir-183 in the primary tumor suggests focal disease at diagnosis. The overexpression of mir-650 in the metastatic lymph node is a recurrence predictor. New studies including functional tests and meta-analyzes may confirm these findings and optimize the use of these miRNAs in clinical practice.